Pengembangan Model Pelatihan Literasi Keuangan Digital Mengimplementasi Model Pembelajaran Langsung Untuk Meningkatkan Pengetahuan dan Keterampilan UMKM - Pratama, Dhimas Wahyu; Hardianto, Deni; Sari, Ayu Perwita (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
Digital financial literacy is a critical competency for Micro, Small, and Medium Enterprises (MSMEs) in navigating the challenges of the digital economy and increasing global competition. This study developed a digital financial literacy training model that integrates active and interactive learning approaches with the utilization of digital technology to enhance financial management skills. The training program was implemented with 27 tenant owners at Teras Malioboro, employing a pre-test and post-test design to measure knowledge and skill acquisition. The findings indicate that the training model is highly effective in enhancing participants’ financial understanding and competence, achieving an average practicality score of 91.13%. The model is considered practical and easily adaptable across diverse MSME contexts due to its interactive and flexible design. Furthermore, this study emphasizes the importance of adopting modern digital tools and methodologies in financial training to address the evolving needs of MSMEs in the digital era. The results provide strategic recommendations for policymakers, educators, and business development practitioners to strengthen digital financial literacy and promote sustainable growth and competitiveness among MSMEs